The Seeker as Weaver: A Matrixial Approach to Feminist Futurity in the Artistic Praxis of Paulina Peavy - Denniston, Rachel (Approaching religion, 2025)
The essay considers the seeker as weaver and positions relationality as central to the experiences of many at the intersections of esotericism and modern art. It invokes the metaphor of weaving to envision a non-static, dislocated and liminal relational positioning by which the seeker weaves worlds: the visible and invisible, material and immaterial, self and other, public and private, and past, present, future. It refers to a relational approach within broader practices around art including art-making, curating and viewing and for which certain forms of art are intertwined with notions of futurity and the potential for societal and spiritual renewal. In doing so, it considers a possible feminine praxis of seekership that connects recent scholarship on seekership with notions of praxis and feminist theory with regards to the relational on the double axis of the social and psychic. It takes as its case study the American artist Paulina Peavy (1901-1999) whose feminist praxis of art-making and curating was guided towards collective change on both a social and spiritual level. Resisting the temptation to conceive of the artist as lone visionary, it establishes her networks (psychic and social) as productive spaces through which she navigated her praxis.